School Health Programme in Sri Lanka: Assessment using WHO's '4S' Framework. (13th November 2019) - Wickramasinghe, N; Lokubalasooriya, A; Vithana, C; Hemachandra, N
Abstract: Background: Sri Lanka has one of the oldest school health programmes (SHP) in the region, which was started in 1918, and at present caters for 70% of adolescents in the country. This study assessed the implementation status of the Sri Lankan SHP. Methods: This review was conducted by a panel of experts adopting a participatory approach. Policies and supporting documents were collected from the relevant sectors of the Ministry of Health and Ministry of Education using electronic and manual search and by visiting institutions/resource persons. The WHO's '4S' Framework; consisting of strategic information (S1), supportive evidence-informed policies (S2), strengthening services for adolescents (S3) and strengthening collaboration with other sectors (S4); was used as the guiding framework to analyse the strengths and weaknesses of the SHP. Results: Having a comprehensive national health information system was the main strength on S1, gaps in timeliness, completeness and accuracy of the data, and the lack of evidence on perceived health needs of school children were the main weaknesses. On S2, Sri Lanka has a strong unifying policy platform supportive of the SHP, but the timeliest need is to finalise the School Health Policy. More than 90% island-wide coverage of school medical inspection was the main strength on S3, while focusing more on physical health and less emphasis on promoting mental health in the existing service package and gaps in the referral/follow-up were the weaknesses. On S4, school staff focusing more on achieving academic-related outcomes and focusing less on health-related activities, undue media and industry influence hindering the promotion of healthy behaviours in school settings were the main challenges. Conclusions: Despite several emerging challenges, the SHP in Sri Lanka is one of the best school health programmes in the region with more than 90% island-wide coverage of health services. Key messages: The SHP in Sri Lanka, which is one of the oldest and the best school health programmes in the region, caters for 70% of adolescents in the country. Assessment of Sri Lankan SHP according to the WHO's '4S' Framework revealed multiple strengths such as comprehensive national health information system and high island-wide coverage.